A new, localised species of purple radiate Senecio (Asteraceae: Senecioneae) from the Sneeuberg massif, South Africa - Clark, Vincent Ralph; Vidal Junior, João De Deus; Vidal Junior, João De Deus; Barker, Nigel Paul (Phytotaxa, 2019)
Senecio stella-purpurea is described as a novel species endemic to the Sneeuberg Centre of Floristic Endemism, Eastern Cape, South Africa. The species was first encountered in 2006 and erroneously identified as S. arenarius in the checklist for the Sneeuberg massif. Closer inspection of the material indicated that this is a novel species clearly distinct in southern Africa’s purple-flowered Senecio flora. Morphologically it is closest to S. glastifolius, S. umbellatus, and S. grandiflorus, but differs by the presence of pinnatisect leaves, solitary flowers, and a densely glandular hairy indumentum along its vegetative parts. Occupying approximately only 200 km2 in the eastern and western Sneeuberg, mostly above 1800 m elevation in Karoo Escarpment Grassland, the IUCN Red Listing status of VULNERABLE is proposed.